The Determinants of Districts/ Cities Spending in Aceh Province: an Analysis of Electoral Districts - Syamni, Ghazali; Ichsan, Ichsan (International Journal of Engineering and Technology, 2026)
The purpose of this study was to examine the determinants of local expenditures (BD) of districts/cities in Aceh Province. This study used secondary data in form of budget realization reports and local expenditures of districts/cities in Aceh province from 2011 to 2015. Data were accessed on legal sites of Central Bureau of Statistic, the financial management and wealth agency of Aceh, and the Ministry of Finance. The result of this study indicated that Regional Gross Domestic Bruto (PDRB), Local Government Revenue (PAD), General Alocation Fund (DAU), and Special Allocation Fund (DAK) influenced local expenditures (BD). Based on the election areas 1 and 2, there were two differences in PDRB, PAD, DAU, and DAK. The other findings of this study revealed that there was a possibility of flypaper effect in the districts/cities of Aceh Province, and will be the further study.